Putting categories in their place: A research agenda for theorizing place in category research. (February 2023) - David, Robert J; Jones, Candace; Croidieu, Grégoire
Existing category research tends to divorce categories from place. When considered at all, place is often relegated to the contextual background. We see at least three important elements of place that can inform our understanding of categories: first, categories are rooted in the materiality of place; second, those who inhabit a place often share a collective identity that can impart meaning to categories; third, places influence the collective action that underlies category processes. Accordingly, we call for categories "to be put in their place" in category research, by attending to the materialities, collective identities, and collective action present in place. We present an integrative framework for future research that links place, categories, and organizational outcomes, and suggest mechanisms that link these constructs.